2017
DOI: 10.1080/19338244.2017.1378606
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of associations between exposures to pesticides and testosterone levels in Thai farmers

Abstract: We conducted a cross-sectional study to assess the relationship between pesticide exposures and testosterone levels in 133 male Thai farmers. Urine and serum samples were collected concurrently from participants. Urine was analyzed for levels of specific and nonspecific metabolites of organophosphates (OPs), pyrethroids, select herbicides, and fungicides. Serum was analyzed for total and free testosterone. Linear regression analyses revealed significant negative relationships between total testosterone and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 45 publications
1
13
2
Order By: Relevance
“…Most participants in the previous study were overweight or obese and a negative correlation between BMI and the testosterone level has been reported [ 40 , 41 ]. Furthermore, an epidemiological study reported that the mean testosterone levels in Thai male farmers and Venezuelan farmworkers were 7.4 and 6.7 ng/mL, respectively, which is similar to the level in our study [ 12 , 16 ]. In comparison with our study, a lower testosterone level (4.5 ng/mL) was reported in Mexican male floriculture workers during intense pesticide spraying, but a similar level (7.6 ng/mL) was reported during less intense pesticide spraying [ 9 ].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Most participants in the previous study were overweight or obese and a negative correlation between BMI and the testosterone level has been reported [ 40 , 41 ]. Furthermore, an epidemiological study reported that the mean testosterone levels in Thai male farmers and Venezuelan farmworkers were 7.4 and 6.7 ng/mL, respectively, which is similar to the level in our study [ 12 , 16 ]. In comparison with our study, a lower testosterone level (4.5 ng/mL) was reported in Mexican male floriculture workers during intense pesticide spraying, but a similar level (7.6 ng/mL) was reported during less intense pesticide spraying [ 9 ].…”
Section: Discussionsupporting
confidence: 90%
“…In comparison with our study, a lower testosterone level (4.5 ng/mL) was reported in Mexican male floriculture workers during intense pesticide spraying, but a similar level (7.6 ng/mL) was reported during less intense pesticide spraying [ 9 ]. This indicates that testosterone levels in our participants were within the normal range according to the World Health Organization guidelines and higher levels were found in males who had worked in agricultural fields for at least 1–20 years [ 9 , 16 , 42 ].…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations